KOMITMEN AFEKTIF DITINJAU DARI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP GURU SD DI SEKOLAH CINTA BUDAYA MEDAN - Michael Lee (Universitas HKBP Nommensen, 2019)
This study aimed to know the relationship between the transformational leadership with affective commitment. The hypothesis in this study was that there was a positive relationship between transformational leadership with affective commitment, in assumption that the higher transformational leadership, then the higher affective commitment and the lower transformational leadership, then the lower affective commitment itself. The subjects that used in this study were the elementary teacher of Cinta Budaya School, in which the population consisted of 87 teachers. Data obtained from the scale to measure transformational leadership and affective commitment. The calculation of the data began by doing a test prerequisite analysis (the test of assumptions) that consisted of a test of normality and a test of linearity. The data analysis in this study used the Product Moment Correlation with SPSS 17 for Windows. The results of analysis showed the correlation coefficient at r = 0.415 of the significance 0.000 (p < 0.05). This showed that there was a positive relationship between transformational leadership with affective commitment. The results of this study indicates that the variable of affective commitment can be predicted by transformational leadership at 17.2 percent and 82.8 percent of the rest are influenced by other factors which not examined in this study. Based on the results of this study, the hypothesis is accepted that there is a positive relationship between transformational leadership with affective commitment